2020
DOI: 10.3390/nano10020278
|View full text |Cite
|
Sign up to set email alerts
|

Partial Oxidation Strategy to Synthesize WS2/WO3 Heterostructure with Enhanced Adsorption Performance for Organic Dyes: Synthesis, Modelling, and Mechanism

Abstract: In this work, a facile oxidation strategy was developed to prepare novel tungsten disulfide/tungsten trioxide (WS2/WO3) heterostructures for adsorbing organic dyes efficiently by combining the hydrophilic property of WO3 and the superior dye affinity of WS2. The structural and elemental properties of the synthesized hybrid materials were systematically investigated, and the results demonstrated the retained flower-like morphology of the primitive WS2 and the successful introduction of WO3. Furthermore, surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Therefore, wastewaters containing this type of dyes were highlighted as one of the most important threatening factors in environmental and public health [2,5]. Different studies have reported that there are several methods for removing dyes from textile wastewaters, including the application of photodecomposition [6], electrolysis [7,8], adsorption [9][10][11][12][13][14][15][16][17][18], oxidation [19], biodegradation [20], combined sonochemical and adsorption [21], coagulation-flocculation [22,23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, wastewaters containing this type of dyes were highlighted as one of the most important threatening factors in environmental and public health [2,5]. Different studies have reported that there are several methods for removing dyes from textile wastewaters, including the application of photodecomposition [6], electrolysis [7,8], adsorption [9][10][11][12][13][14][15][16][17][18], oxidation [19], biodegradation [20], combined sonochemical and adsorption [21], coagulation-flocculation [22,23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among wastewater treatment technologies, the adsorption is considered the most inexpensive, fast and simple operation method [182]. Recently, researchers are focusing on the application of TMDC-based material in adsorption technology.…”
Section: Adsorption For Wastewater Treatmentmentioning
confidence: 99%
“…Li et al [ 187 ] stated that the application of MoS 2 adsorbent can increase the adsorption capacity in removing organic dye. An alternative facile oxidation strategy was proposed by Li et al [ 182 ] to synthesize tungsten disulphide/tungsten trioxide (WS 2 /WO 3 ) heterostructures to remove RhB molecules from wastewater (see Figure 6 a). This strategy has contributed to higher adsorption capacity through manipulating the surface property.…”
Section: Tmdc Materials For Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, water pollution has become an international environmental problem that constricts the development of human health, economy and sustainability [ 1 , 2 ]. To solve this problem, various efficient technologies have been developed and employed to purify wastewater, such as photocatalysis, adsorption, chemical precipitation, and membrane filtration [ 3 , 4 , 5 , 6 ]. Among them, photocatalysis has been regarded as a promising approach due to its convenient operation, effective remediation and low environmental impacts [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%